Does pain at an earlier stage of chondropathy protect female mice from structural progression after surgically induced osteoarthritis? - von Loga, IS; Batchelor, V; Driscoll, C; Burleigh, A; Chia, S-L; Stott, B; Miotla-Zarebska, J; Riley, D; Dell'Accio, F; Vincent, TL (Wiley, 2020)
Objective Female C57BL/6 mice exhibit less severe chondropathy than male mice. This study was undertaken to test the robustness of this observation and explore underlying mechanisms.